Análisis de las actitudes hacia la actividad minera en la comunidad de Combayo, región Cajamarca - Vásquez pacheco, Jorge L (2019)
This is a descriptive study that applies a cross research methodology through the application of an original scale of attitudes, likert like, composed originally of 32 reagents, reduced to 29 items after the statistical analysis through the item-test correlation. The scale obtained a cronbach alpha coefficient of, 938 thereby determining the consistency and validity for the purpose of this study. The participants were 120 people natives from the combayo’s community, region cajamarca, ranging in age from 18 to 60 years (men and women) selected randomly. no preference was given to any gender and all doubts were resolved in an individual manner. also, after application of the instrument brief interviews were conducted with a subgroup (30) randomly chosen in order to complement and contrast the information obtained, thus disclosing whether the villager from combayo has a basis for the position taken. We looked into five factors: Quality of life, community development, community prospecting, psychological wellbeing, and physical wellbeing. Where indicators serve to establish approval levels on mining, with the following results: For 80% of the subjects mining is unfavorable, for 14% of the subjects mining is favorable, and for 6% of the subjects the influence of mining is neutral. We conclude that despite the negative attitude towards mining in this community, residents accept it since they generally perceived that this activity could contribute to their welfare but at the cost of their quality of life (First Factor), but it is of their greater consideration (scores of arithmetic mean) the development of their community (second factor), the communal prospects (third factor), the psychological wellbeing (fourth factor), and physical wellbeing (Fifth Factor). nevertheless, such consideration falls on contributing to improve their quality of life. one can see that the commoners of combayo are more interested in obtaining short-term results and immediate satisfaction regarding the benefits expected from the development of mining activities in their community, which shows the presence of cognitive dissonance in that community since they would be recognizing their needs and also the cost of meeting them.